2005
DOI: 10.1063/1.1857652
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetic study of domain-wall pinning characteristics with grooves in thin films

Abstract: The pinning characteristics of a 180° domain wall with grooves are investigated using the micromagnetic simulation. The depinning fields required to pull the wall out of the grooved region were strongly related to the pinning characteristics at each step edge. The depinning field difference between the wall movement directions was improved by the increase of the lower depinning field compared to that with the steplike thickness change. It was also found that the depinning fields for various groove widths were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…5 In the previous work, micromagnetic simulation has reported that steplike thickness change along a domain wall can produce wall pinning in an in-plane magnetization thin film. 6,7 The simulation results have indicated that a bidirectional pinning effect for magnetic fields applied along the magnetic domain was obtained at the step.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…5 In the previous work, micromagnetic simulation has reported that steplike thickness change along a domain wall can produce wall pinning in an in-plane magnetization thin film. 6,7 The simulation results have indicated that a bidirectional pinning effect for magnetic fields applied along the magnetic domain was obtained at the step.…”
Section: Introductionmentioning
confidence: 95%
“…[6][7][8][9] As illustrated in Fig. 1, a steplike thickness change ͑⌬h͒ along the domain wall ͑x direction͒ is assumed to clarify the wall-pinning characteristics with thickness change.…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation